Model Predictive Controller Design for Uncertain Bilinear Systems and an Application to Control a Continuously Stirred Tank Reactor with Hydrolysis Acetic Anhydride - Mai, Thi Doan Thanh; Nguyen, Vi Anh Tuan; Tran, Dinh Vung; Doan, Quang Vinh (Old Journal, 2017)
The paper proposes a predictive control method for a bilinear MIMO system with slow varying uncertain parameters. This proposed predictive control method operates under the principle of setting predictive model based on a linearization along the trajectories of the bilinear system and estimated uncertain parameters. To increase the capability to follow the setpoint signal, a compensation control for signal components has also been added. The input compensation design is used to improve the tracking problem. The input compensation is designed based on an adaptive mechanism. An application of the control algorithm in continuously stirred tank reactor with hydrolysis acetic anhydride is given to illustrated the tracking effectiveness.